Wykorzystanie własności funkcji liniowej do konstruowania strategii opcyjnych - Stolorz, Beata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article presents how the properties of the linear functions could be used to the construction of option strategies. An option can be represented as a function of its profit at expiry. Each complex strategy is a combination of basic strategies. Thus, the function of profit of complex option strategies is a linear combination of function of an income of basic strategies with coeficients that are integral non-negativ numbers. The method was presented on the basis of construction and analysis of spread option strategies. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 408-414